The impact of public sector accounting implementation and internal supervision on the performance of government institutions - Rian Pratikto Hidayatulloh; Novi Ernawati; Bayu Karunia Putra; M. Ulul Azmi; Kurnia Wati (Journal of Economic Resilience and Sustainable Development, 2025)
Background: This study aims to analyze the influence of public sector accounting implementation and internal control on the performance of government agencies at the Office of the Ministry of Religious Affairs in East Lombok Regency. Methods: This research adopts a correlational design with a quantitative approach. The data were gathered through surveys, interviews, and document analysis. The data were analyzed using multiple linear regression, involving two independent variables public sector accounting (X1) and internal control and one dependent variable, namely government agency performance (Y). Findings: Based on the data analysis and discussion, the findings are as follows: Public sector accounting has a significant positive impact on agency performance, as evidenced by a t-test significance value of 0.008 (p < 0.05). Internal control also shows a significant positive effect, with a t-test significance value of 0.000 (p < 0.05). Collectively, public sector accounting and internal control have a significant influence on agency performance, as indicated by an F-test significance value of 0.000 (p < 0.05). Conclusion: The study indicates that public sector accounting and internal control together contribute 35.2% to the performance of government agencies at the Office of the Ministry of Religious Affairs in East Lombok Regency. The remaining 64.8% is attributed to other factors not explored in this research. Novelty/Originality of this article: This study shows that the simultaneous application of public sector accounting and internal control significantly influences the performance of government agencies, particularly in the context of the Ministry of Religious Affairs in regions where research has rarely been conducted.